Fabrication of bioactive polypyrrole microelectrodes on insulating surfaces by surface-guided biocatalytical polymerization1. Issue 82 (5th September 2015) - Galán, T.; Lagunas, A.; Martinez, E.; Samitier, J.
<x xml:space="preserve">Abstract</x> A novel surface-guided biocatalytical polymerization procedure for polypyrrole microelectrodes is developed without the requirement of cleanroom facilities, it can be straightforwardly scaled up and is compatible with in situ biomolecule entrapment.